2022
DOI: 10.1111/ijfs.15940
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bread fortified with Dictyophora Indusiata powder: evaluation of quality attributes, antioxidant characteristics and bread staling

Abstract: This study aimed to investigate the physical, nutritional, antioxidant and sensory properties, as well as the starch digestibility of wheat bread containing Dictyophora Indusiata powder (DIP) as a functional addition. Results showed that though the specific volume of wheat breads decreased with the addition of DIP, the chewiness showed an increasing trend. The wheat bread containing DIP showed significantly higher (P < 0.05) content of protein and dietary fibre compared to the control bread. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The hardness value increased almost two times for 4 days of storage for all samples. Liu et al (2022) observed the same trend when bread was fortified with Dictyophora indusiata powder and suggested that it may be explained by the contraction and densification of the gluten network structure caused by a decrease in moisture content. In addition, Tae et al (2015) report that adding burdock flour to bread significantly increased its crumb hardness.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The hardness value increased almost two times for 4 days of storage for all samples. Liu et al (2022) observed the same trend when bread was fortified with Dictyophora indusiata powder and suggested that it may be explained by the contraction and densification of the gluten network structure caused by a decrease in moisture content. In addition, Tae et al (2015) report that adding burdock flour to bread significantly increased its crumb hardness.…”
Section: Resultsmentioning
confidence: 78%
“…However, as storage time increased, the 9% BRF substituted samples underwent more substantial changes in hardness, springiness, chewiness, and cohesiveness than bread samples with lower BRF levels and the control with no added BRF. In addition, dietary fiber appeared to have a better ability to absorb and store water, preventing+ moisture from moving from the crumb to the bread crust, as evidenced by the textural parameters over a storage period of 5 days by adding D. indusiata powder (Liu et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard curves of starch hydrolysis rate and time were plotted to simulate this equation (Liu et al ., 2022b). The area under the curve (AUC) indicates the effect of pizza digestion on blood glucose.…”
Section: Methodsmentioning
confidence: 99%